THE EMPOWERMENT OF YOUTH LOCAL ORGANIZATION IN TOURISM MANAGEMENT AT WARNASARI VILLAGE, PANGALENGAN DISTRICT, BANDUNG REGENCY - Umi Hani; Ika Sari Hastuti; Erti Dinihayati (Universitas Pasundan, 2021)
The purpose of Karang Taruna is a form of youth organization and actively involved in all community activities because it is considered capable of bringing change to improve the welfare of its community. It participate in the tourist management attractions in the Warnasari village which has a lot of natural tourism potential and can improve the village economic level, one of which is the natural tourist attraction of Situ Cileunca which has many rides that can be enjoyed by tourists, tourist attractions are managed by investors professionally, but Karang Taruna is involved in technical management. The problems is the low competence of youth in tourism management, out of work and unable to create jobs, the cause being the low level of education and skills. This study aims to determine the extent of empowerment in seeing the potential of Karang Taruna in advancing tourism and its impact on improving the community's economy. The method used in this research is descriptive qualitative with data collection through in-depth interviews, observation, and documentation studies. The results show that the ability of youth organizations in tourism management is still weak, especially their management capabilities, management is still mostly carried out by investors, youth organizations are only involved in managing infrastructure. The Karang Taruna is also weak in mastering technology and foreign languages. The challenge is that required to master technology and language as well as possible to communicate with investors and the community in order to improve their economic empowerment